The association between published accounting data and the behaviour of share prices - Knight, Rory Francis Murphy (School of Economics, 2020)
This dissertation presents a variety of empirical studies in financial accounting with an emphasis on the association between published accounting data and share prices. These studies are the first attempt at empirical research in accounting in South Africa. There has been an alarming lack of research in this discipline in this country and only 14 doctorates in the accounting field have ever been conferred by South African universities. The major aim of the dissertation is to contribute to the understanding of the usefulness of accounting data and the effect that certain financial disclosures (and non-disclosures) have on share prices and consequently on the wealth of the users and potential users of these data. An essential premise of this thesis is that the primary purpose of financial reporting is the provision of information useful for economic decision making.